Corporate ESP Training: Challenges and Recommendations - Hening Dian Paramita (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2018)
This paper examines the challenges in corporate English for Specific Purposes (ESP) training and discovered that immature course planning is the root of the problems. It analyzes the absence of systematic criteria to design an ESP training and the parties in charge of conducting needs analysis, developing course and test materials as well as designing course syllabus. Finally, it gives recommendations to corporate clients and ESP training providers for improving the quality of their training programs and to researchers to advance the research of ESP training in professional settings.